2016
DOI: 10.1016/j.neuroimage.2016.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of letter-specific responses in time, space and current polarity using magnetoencephalography

Abstract: Recent neurophysiological evidence suggests that a hierarchical neural network of low-to-high level processing subserves written language comprehension. While a considerable amount of research has identified distinct regions and stages of processing, the relations between them and to this hierarchical model remain unclear. Magnetoencephalography (MEG) is a technique frequently employed in such investigations; however, no studies have sought to test whether the conventional method of reconstructing currents at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
74
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(87 citation statements)
references
References 31 publications
11
74
2
Order By: Relevance
“…This sample size was selected based on previous studies using the same MEG machine (e.g. (Gwilliams and Marantz, 2015;Gwilliams et al, 2016)). They were recruited from the New York University Abu Dhabi community and were compensated for their time.…”
Section: Materials Creation (Common To Both Experiments)mentioning
confidence: 99%
“…This sample size was selected based on previous studies using the same MEG machine (e.g. (Gwilliams and Marantz, 2015;Gwilliams et al, 2016)). They were recruited from the New York University Abu Dhabi community and were compensated for their time.…”
Section: Materials Creation (Common To Both Experiments)mentioning
confidence: 99%
“…Previous studies, on English words, have found support for automatic form-based decomposition (Fruchter, Stockall, & Marantz, 2013), morphological decomposition indexed by TPL (Solomyak & Marantz, 2010), as well as effect of morphological complexity in a corresponding right hemispheric response (Zweig & Pylkkänen, 2009 the first would be associated with orthographic processing and the second with more abstract lexical processing (Gwilliams et al, 2016). In the present study, to ensure robust across-participants matching, the letter-string response was modeled as a single source in the more traditional fashion (Tarkiainen et al, 1999), and it may thus not capture a possible second component in a more anterior region that might be linked to lexicality or morphology.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the functional role of the occipito‐temporal activity in morphological processing seems to remain somewhat unclear. Interestingly, a recent study, using English words as stimuli and applying a special variant of distributed source modeling, suggests that the occipito‐temporal response may in fact consist of two functionally and temporally distinct components: the first would be associated with orthographic processing and the second with more abstract lexical processing (Gwilliams et al, 2016). In the present study, to ensure robust across‐participants matching, the letter‐string response was modeled as a single source in the more traditional fashion (Tarkiainen et al, 1999), and it may thus not capture a possible second component in a more anterior region that might be linked to lexicality or morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations